The Development of Syllable Method Through Sound Reposition to Improve Early Reading Skill Ability of Mild Mentally Retarded Class III at SLB C Dharma Bhakti Dharma Pertiwi Bandar Lampung - Adlina, Mia Nur; Rochyadi, Endang; Sunardi, Sunardi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
The ability to read is a basic cognitive ability needed by everyone and is a complex activity because it requires visual ability, memory, auditory, and good pronunciation. Mild retardation children find it difficult to remember new things so that the majority of them have difficulty in differentiating simple syllables, words, and phrases that impact the ability to read the beginning. The current reading method has not yet accommodated the constraints faced. Therefore, it is necessary to find a suitable method for them by developing syllable method through repositioning sound. The purpose of this study is to determine whether the syllable method through sound repositioning can improve the reading ability of children with mild intellectual disabilities. This research uses SSR experimental method with an A-B-A design. The data collection is done by giving a preliminary reading test consisting of the ability to read syllable patterned kv- kv, simple sentences, and simple paragraphs. Significantly the results of this study were able to improve the reading ability of early childhood with mild intellectual disability class III in SLB C Dharma Bhakti Dharma Pertiwi Bandar Lampung. The conclusion of the syllable method through sound repositioning can improve the reading ability of the beginning especially for the children with mild intellectual disability and apply to the subject under study. Recommendations of syllable methods through repositioning sounds can be helped through supporting media such as colored card media, concrete objects, and interactive drawings, the child is easy to understand and more attention to the child to foster motivation to learn.